OJEBETA “THE SELF AWAKENED” IN BUCHI EMECHETA’S THE SLAVE GIRL - B., Mary Stella Ran; Reddy R., Poli (International Journal of Research -GRANTHAALAYAH, 2018)
The novel “The Slave Girl” by Buchi Emecheta exposes the plights of African women and portrayal of their struggle as slaves and ultimately how they come up the problem and becomes a self-awakened. In this paper, one can see Ojebeta starting her life as a slave and finally becomes an owner of a house by passing so many phases of life as a slave. In the beginning, she is sold into domestic slavery by her own brother. She has become the victim to her brother’s traits. She has become a scapegoat to the plans of African patriarchy. The intention of Buchi Emecheta is to recreate the image of women through feminism. Emecheta’s fiction is blended with reality representing socio historical elements of the prevailing society and its environment besides questioning the pathetic conditions of the people in general and women in particular. One can observe the narration of innocence of childhood grown into adulthood by attaining certain amount of freedom with the Christian education which she has received with which she has attained a small degree of self-awareness.